Analysis of professional basketball team training - comparing drill types on different playing positions - Djuricic, N.; Montalvo, A.; Navarro, R. M.; Muñoz Andradas, G.; Serrano, C. (Journal of Human Sport & Exercise, 2025)
This study investigates the external load experienced during various game-based drills (GBD) in professional basketball, focusing on the most commonly used formats during the competitive season. External load metrics such as total distance (TD), player load (PL), high-speed running (HSR), accelerations (HI ACC), decelerations (HI DEC), jumps (HI JUMP), and landings (HI LAND) were assessed across different GBD types, including 5vs5, 5vs0, and variations in court size. A total of 12 male professional basketball players participated in the study, with data collected over 46 sessions. Results indicated that 5vs5 and 5vs0 formats were most prevalent, with significant differences in external load depending on court size, opposition presence, and player position. Larger court sizes and drills involving opposition resulted in higher physical demands, particularly in PL, and high-intensity actions, where drills without opposition showed high demands in HSR and HI LAND. Positional differences were observed, with guards and forwards exhibiting greater HSR and higher acceleration/deceleration values compared to centers. These findings provide insights into the external demands of GBD, highlighting the importance of customizing training load based on positional roles and the nature of the drills. The study underscores the need for further research to incorporate both external and internal load measures, including data from official games, to enhance understanding of how GBD formats influence player performance and adaptation.